2019
DOI: 10.1155/2019/7364213
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Angiotensin-I-Converting Enzyme Inhibitory Peptides Derived from Camellia oleifera Abel Seed Meal Hydrolysate

Abstract: China is a large country that produces Camellia oleifera Abel seed meal (COASM), a by-product of tea-seed oil, which is only used as an organic fertilizer, resulting in a serious waste of high-quality resources. The preparation of the ACE inhibitory peptide from COASM and the study of its functional properties are of practical importance in improving the comprehensive utilization of COASM. Our manuscript presents an optimized preparation of ACE inhibitory peptides with alkaline protease and enzyme kinetics par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…A significant increase in ACEi activity (i.e., low IC50) was observed by employing lower MWCOs to the permeate produced under optimum conditions (Figure 6). This trend has also been reported in various studies (Herrera Chalé et al, 2014;Tuz and Campos, 2017;Yao et al, 2019;Sitanggang et al, 2021b;Kurniadi et al, 2023;Sitanggang et al, 2023). The strongest ACEi activity was found in the lowest fraction (<2 kDa), measuring 0.23 µg protein/mL.…”
Section: Ace Ic50 Of Different Peptide Fractionssupporting
confidence: 87%
“…A significant increase in ACEi activity (i.e., low IC50) was observed by employing lower MWCOs to the permeate produced under optimum conditions (Figure 6). This trend has also been reported in various studies (Herrera Chalé et al, 2014;Tuz and Campos, 2017;Yao et al, 2019;Sitanggang et al, 2021b;Kurniadi et al, 2023;Sitanggang et al, 2023). The strongest ACEi activity was found in the lowest fraction (<2 kDa), measuring 0.23 µg protein/mL.…”
Section: Ace Ic50 Of Different Peptide Fractionssupporting
confidence: 87%
“…Considering the amount of proteins for the skims (Table 5.2) and degree of hydrolysis (DH) did not present significative differences (p>0.05) when using the same protease (except for (C+H) + NP that presented higher DH) (Souza Almeida et al, 2021), the increase in ACE inhibition probably is not associated with further proteolysis, but instead, it could be associated with protein structural modification over time. This result agrees with the observed results for Camellia oleifera Abel seed meal (COASM), where authors demonstrated that the degree of hydrolysis was not positively correlated with the ACE inhibition rate (Yao et al, 2019). Therefore, the differences found may be associated with protein structural modification or type of phenolics released during the extractions, reinforcing the activity of both peptides and phenolics present in the coffee extracts.…”
Section: Ace Inhibitory Activitysupporting
confidence: 92%
“…The mass deviation of the synthesized peptide was 0.0396%. With an 89% purity, this indicates that the identity of the synthetic peptide was acceptable to be used for further biochemical assays such as antioxidant assays, enzyme kinetic reactions, and semi-quantitative applications [14].…”
Section: Peptide Synthesis By Spps Approachmentioning
confidence: 91%